The design of the facility level module of an experimental PCB assembly facility - Wang, Tek Kee. (2009)
This thesis explores the process of implementing computer integrated manufacturing and the issue of computer support of concurrent engineering. The research uses a research facility in GINTIC Institute of Manufacturing Technology, namely the GINTIC Experimental PCB Assembly Facility, as an example CIM implementation. The research involves the design of the Facility Level Control Module for the EPCBAF. The Facility Level is the level in the CIM hierarchy that addresses the design and planning functions in an enterprise.